Impact of Microbially Enhanced Coalbed Methane on the Pore Structure of Coal - Gao, Di; Guo, Huiling; Guo, Bianqing; Tan, Kaili; Ren, Hengxing (Frontiers in Earth Science, 2022)
Microbially enhanced coalbed methane (MECBM) has important theoretical and practical significance for reforming coal reservoir structure, alleviating greenhouse effects and energy crises and developing new sources of clean energy. In this study, No. 3 coal seams in Qinshui Basin were taken as research objects to analyze the pore structure characteristics after microbial treatment by means of low-temperature nitrogen adsorption (LTNA), mercury porosimetry (MP), and isothermal adsorption/desorption experiments. The results showed that after bioconversion, the specific surface area and pore volume increased from 1.79 m2/g and 0.0018 cm3/g to 4.01 m2/g and 0.0051 cm3/g respectively under liquid nitrogen testing; however, the specific surface area was reduced from 5.398 m2/g to 5.246 m2/g and the pore volume was increased from 0.053 cm3/g to 0.0626 cm3/g under MP. The fractal dimension based on the LTNA data indicated that the fractal dimension of micropores and minipores was increased from 2.73 and 2.60 to 2.89 and 2.81, however the fractal dimension of meso-macropores was decreased from 2.90 to 2.85. The volatile matter and fixed carbon were both reduced from 6.68% and 78.63% to 5.09% and 75.63%, and the Langmuir volume and Langmuir pressure were increased from 34.84 cm3/g and 2.73 MPa to 36.34 cm3/g and 3.28 MPa, respectively. This result indicated that microorganism participated in the degradation of coal reservoir and promoted the production of methane gas, the meso-macropores were more obviously modified by microorganism, so that the pore diameter stabilized, the pores became smoother, the specific surface area decreased, and the pore volume increased. These are more beneficial to the adsorption and production of coalbed methane (CBM) after microbial treatment.